Cancer and Cardiovascular Disease A Concise Clinical Atlas (Springer International Publishing, 2018)
The atlas provides a clear, concise, yet comprehensive review of common cardiovascular diseases occurring in patients with cancer. Cancer and cardiovascular disease are the two most common conditions worldwide. In clinical practice we frequently encounter patients who have established cardiovascular disease and subsequently develop cancer or are survivors of cancer with subsequent cardiovascular complications related to chemotherapy and or radiation. Most of the chapters are case based, followed by images and a discussion on current (evidence based, wherever available) investigations and treatment outline.